Empirical methods for determining shaft bearing capacity of semi-deep foundations socketed in rocks - S. Rezazadeh; A. Eslami (Journal of Rock Mechanics and Geotechnical Engineering, 2017)
Semi-deep foundations socketed in rocks are considered to be a viable option for the foundations in the presence of heavy load imposed by high-rise structures, due to the low settlement and high bearing capacity. In the optimum design of semi-deep foundations, prediction of the shaft bearing capacity, rs, of foundations socketed in rocks is thus critically important. In this study, the unconfined compressive strength (UCS), qu, has been applied in order to investigate the shaft bearing capacity. For this, a database of 106 full-scale load tests is compiled with UCS values of surrounding rocks, in which 34 tests with rock quality designation (RQD), and 5 tests with rock mass rating (RMR). The bearing rocks for semi-deep foundations include limestone, mudstone, siltstone, shale, granite, tuff, granodiorite, claystone, sandstone, phyllite, schist, and greywacke. Using the database, the applicability and accuracy of the existing empirical methods are evaluated and new relations are derived between the shaft bearing capacity and UCS based on the types of rocks. Moreover, a general equation in case of unknown rock types is proposed and it is verified by another set of data. Since rock-socketed shafts are supported by rock mass (not intact rock), a reduction factor for the compressive strength is suggested and verified in which the effect of discontinuities is considered using the modified UCS, qu(modified), based upon RMR and RQD in order to take into account the effect of the rock mass properties.